Attitudes of medical students in Croatia toward rural medicine education and practice - Mrduljaš-Ðujić, Nataša; Radić, Ivana; Bašić Marković, Nina; Vrgoč, Toni; Buljubašić, Maja (Frontiers in Medicine, 2025)
IntroductionRecruiting and retaining doctors in rural areas is challenging. In Croatia, medical school curricula lack content on rural medicine and specialized training for rural practice. This study explores the opinions and attitudes of first- and sixth-year medical students in all four medical schools in Croatia regarding working in rural areas.MethodsAn online questionnaire was administered to Croatian medical students in their first and final years between January 2022 and February 2023. Responses were obtained from 690 participants from the Universities of Osijek, Rijeka, Split, and Zagreb. The cross-sectional study included 13 questions, with 5 on socio-demographic data. Data were analyzed using descriptive statistics and non-parametric tests (chi-square) to assess group differences.ResultsCompared to first-year students, final-year students feel less prepared by their education for rural practice (χ2 = 84.287; P = 0.000) but are more interested in working in rural areas (χ2 = 26.810; P = 0.000). Most students believe rural doctors need additional financial incentives, with this belief significantly stronger among final-year students (χ2 = 14.192; P = 0.000). Both groups agree that rural doctors face poor working conditions (χ2 = 1.524; P = 0.217). No statistically significant differences were found regarding job interest outside city centers (χ2 = 2.041; P = 0.564) or choosing rural medical practice (χ2 = 4.795; P = 0.187) among medical students from the Universities of Osijek, Rijeka, Split, and Zagreb. Students from rural settlements were more often interested in jobs outside the city center (72.1%) compared to those from smaller towns (60.6%), [χ2(1) = 5.142, p = 0.023] and larger cities (44.1%), [χ2(1) = 28.978, p = 0.000].ConclusionAlthough Croatian medical students show interest in working in rural areas, their education lacks sufficient preparation for the unique challenges of rural practice. They view the current conditions for rural doctors as inadequate and believe that additional financial incentives are necessary. Interest in rural practice is consistent across medical faculties in Croatia, with students living in rural areas showing a higher interest in working there.